KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) - Nursiah; Uci Mahlisa (Jurnal Genta Mulia, 2024)
Students have difficulty in learning mathematics because they do not understand the basic concepts of mathematics. one of the causes is because mathematics is taught as something abstract, monotonous and less interesting. Innovations and alternatives in improving students' mathematical understanding are needed, one of them is technology-based learning. This is in line with the 2013 curriculum requirements to integrate technology into learning process. The integration can be done with TPACK-based learning that is merging of Technology, Pedagogy, and Content Knowledge. Learning will also be more meaningful for students if teachers can present contextual and realistic problems, ie with a realistic mathematical approach. One of the material studied by the students is the equation and quadratic function related to the function graph in cartesian coordinate system.. Although drawing coordinate points in the Cartesian field has already been studied by students at the junior level, students' understanding of the material is still low, as it requires reasoning and skill. The purpose of this research is to know how the students' mathematical understanding through TPACK realistic mathematics approach. The method used was Design Research at the Pre Prototyping Research phase involving 25 students of X MAN 1 Meulaboh. Data were collected through student answer analysis. The results obtained that the learning through realistic mathematical approach based on TPACK can help students understand the material graph of quadratic functions well, but not yet perfect. This is seen in each indicator of understanding that can be achieved well. However, the indicator of ability to apply the concept algorithm and the ability to present the concept in various forms of representation is still low.